Maternal mortality and its prominence in the Syrian Arab Republic: Challenges, efforts, and recommendations. (October 2022) - Butt, Malaika Saeed; Tharwani, Zoaib Habib; Muzzamil, Muhammad; Rafi, Hania Mansoor
Abstract: WHO has brought to light how the Maternal Mortality Ratio is alarmingly high in countries like Syria because women lack basic necessities such as access to proper healthcare, resources, and information. With the ongoing war, COVID-19 pandemic, and other resultant factors are converging to further exacerbate Syria's current collapsing situation. Leading to an increasing number of maternal mortality cases, with the country's economy and its disparities making it nearly impossible for Syria to recover. In the wake of these problems piling up, Syria requires immediate preventative measure to be put into place to avoid further crises complications, and mortalities.